MICROFOSILES CALCAREOS DE LA FORMACION RANQUILES (CRETACICO INFERIOR) EN LA PROVINCIA DE NEUQUEN, ARGENTINA (Ameghiniana, 2013)
The first calcareous microfossils (ostracods, charophytes and foraminifers) found in Ranquiles Formation suggest Lower Cretaceous age for it; and, for some levels, brackish-continental environment. Four new species of ostracods are described.